PENINGKATAN KEMAMPUAN KEPALA SEKOLAH DALAM PENGAMBILAN KEPUTUSAN - Puji Rahayu (Universitas Negeri Padang, 2014)
The goal of this research are to see informations abaut headmaster to decision making by school principal. The result of this research are the headmaster decision by school principalin the state junior high school in Yayasan Mutiara Gambut stay in goog enough category. Kata kunci : Pengambilan keputusan